Solve for a (complex solution)
\left\{\begin{matrix}\\a=x\text{, }&\text{unconditionally}\\a\in \mathrm{C}\text{, }&x=\beta \end{matrix}\right.
Solve for a
\left\{\begin{matrix}\\a=x\text{, }&\text{unconditionally}\\a\in \mathrm{R}\text{, }&x=\beta \end{matrix}\right.
Solve for x
x=\beta
x=a
Graph
Share
Copied to clipboard
x^{2}-\left(ax+\beta x\right)+a\beta =0
Use the distributive property to multiply a+\beta by x.
x^{2}-ax-\beta x+a\beta =0
To find the opposite of ax+\beta x, find the opposite of each term.
-ax-\beta x+a\beta =-x^{2}
Subtract x^{2} from both sides. Anything subtracted from zero gives its negation.
-ax+a\beta =-x^{2}+\beta x
Add \beta x to both sides.
\left(-x+\beta \right)a=-x^{2}+\beta x
Combine all terms containing a.
\left(\beta -x\right)a=x\beta -x^{2}
The equation is in standard form.
\frac{\left(\beta -x\right)a}{\beta -x}=\frac{x\left(\beta -x\right)}{\beta -x}
Divide both sides by -x+\beta .
a=\frac{x\left(\beta -x\right)}{\beta -x}
Dividing by -x+\beta undoes the multiplication by -x+\beta .
a=x
Divide x\left(-x+\beta \right) by -x+\beta .
x^{2}-\left(ax+\beta x\right)+a\beta =0
Use the distributive property to multiply a+\beta by x.
x^{2}-ax-\beta x+a\beta =0
To find the opposite of ax+\beta x, find the opposite of each term.
-ax-\beta x+a\beta =-x^{2}
Subtract x^{2} from both sides. Anything subtracted from zero gives its negation.
-ax+a\beta =-x^{2}+\beta x
Add \beta x to both sides.
\left(-x+\beta \right)a=-x^{2}+\beta x
Combine all terms containing a.
\left(\beta -x\right)a=x\beta -x^{2}
The equation is in standard form.
\frac{\left(\beta -x\right)a}{\beta -x}=\frac{x\left(\beta -x\right)}{\beta -x}
Divide both sides by -x+\beta .
a=\frac{x\left(\beta -x\right)}{\beta -x}
Dividing by -x+\beta undoes the multiplication by -x+\beta .
a=x
Divide x\left(-x+\beta \right) by -x+\beta .
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}